Neurogenic Stunned Myocardium Associated with Acute Spinal Cord Infarction: A Case Report - Gillian A. Beauchamp; Jason T. McMullan; Jordan B. Bonomo (Case Reports in Critical Care)
Introduction. Neurogenic stunned myocardium (NSM) is a reversible cardiomyopathy resulting in transient left ventricular apical ballooning presumed to result from catecholamine surge occurring under physiologic stress. Acute spinal cord ischemia is a rare ischemic vascular lesion. We report a case of neurogenic stunned myocardium occurring in the setting of acute spinal cord infarction. Methods. Singe case report was used. Results. We present the case of a 63-year-old female with a history of prior lacunar stroke, hypertension, chronic back pain, and hypothyroidism who presented with a brief episode of diffuse abdominal and bilateral lower extremity pain which progressed within minutes to bilateral lower extremity flaccid paralysis. MRI of the spinal cord revealed central signal hyperintensity of T2-weighted imaging from conus to T8 region, concerning for acute spinal cord ischemia. Transthoracic echocardiogram was performed to determine if a cardiac embolic phenomenon may have precipitated this ischemic event and showed left ventricular apical hypokinesis and ballooning concerning for NSM. Conclusion. Neurogenic stunned myocardium is a reversible cardiomyopathy which has been described in patients with physiologic stress resulting in ventricular apical ballooning. Our case suggests that it is possible for neurogenic stunned myocardium to occur in the setting of acute spinal cord ischemia.